Impact of herding on individual investor’s investment decision - Kaleem Ullah; Shahid Jan Kakakhel (Elementary Education Online, 2023)
The presumption of the rationality of conventional finance has long been questioned by behavioral finance. Recently many non-financial factors including human personality traits and social environment surrounding decisions to be made have emerged.In this study, the influence of selected behavioral biases on investment decision-making is done.Data was collected through a questionnaire, circulated to a representative sample (n=475) of Pakistani stock exchange investors. In this study descriptive stat, correlation and regression are used for analysis. Our results show that behavioral biases significantly affect the investment decisions of an individual investor. Theoretically, the research advocated the inclusion of herding in investment decisions. Results show that investors understand their emotional influences while growing self-control and investment analysis skills. Further analysis can use psychological bias and other accounting data metrics such as Earning per Share (EPS) to assess herding behavior in investment decision-making, along with the prejudices faced by investors when making investments